Ngesti Utomo Rodhat Dance as a Means of Bersih Sendang Dadapan Ritual in Boyolali Regency - Suharji, S. (Harmonia: Journal of Arts Research and Education, 2014)
Rodhat dance is one of the dances used for Bersih Sendang ritual in the slope of Mount Merbabu. This study investigated the role of Rodhat dance in Bersih Sendang ceremony. This study was conducted using qualitative method, and the data collection techniques were observation, interview, and documentation. The approach used in this study was anthropological approach. Data analysis techniques in this study were reduced, reformation, and conclusion. The result of this study shows that Rodhat dance is a folk dance used as a means of ritual in the society. The accompaniments of the ritual are sesaji (offerings) and ujuban (prayer). Acculturation occurred due to the mix of the ancestorâs worship tradition and Islamic tradition. The dance is conducted every year to free the spring from bad attitudes of human beings, so that the water in the spring is always available for the welfare of the local society. With the plentiful water, the people is happy because their farm is irrigated. Bersih sendang ritual is an expression of gratitude to The Creator who has given His gift to the people living in Gunungan Lor, Jeruk village, Sela sub-district, Boyolali regency.